Influence of Occupational Stress on Quality Family Relationship among Clergy: A Case of Christ is the Answer Ministries, Kenya - Makena, Veronica Kaari; Wambugu, Anne G.; Chiroma, Nathan H. (European Scientific Journal, ESJ, 2023)
The role of clergy can be demanding, as they are tasked with providing spiritual guidance and support to their congregation. This responsibility can result in occupational stress, which can affect the clergy and their family relationships. This study investigated the influence of occupational stress on quality family relationships among clergy in Christ Is the Answer Ministries, Kenya (CITAM). A pragmatist lens which informs the adoption of mixed methods research design was used. Out of a sample size of 135, 115 respondents comprising 57 pastors, 40 spouses, and 18 children participated in the study. Ethical considerations were adhered to by receiving the necessary approvals and licenses before commencing the study. Primary data was collected using questionnaires and focus group discussions which were all done online. Quantitative data were analyzed using the linear regression technique in SPSS Version 28 and presented through tables. The qualitative data were transcribed and analysed using a thematic analysis approach with the identification of key themes. Findings showed that the clergy families have high-quality family relationships (x̅=3.4635, x = .37655). Thematic analysis revealed that having intentionality and maintaining clear boundaries between work and personal life would help clergy improve the quality of their family relationships. The study recommended that churches should collaborate with family therapists to offer therapy sessions to all members of the clergy.